Magnetic resonance imaging features of epididymal and/or testicular tuberculosis: a case series - Bowen Yang; Renbing Zhou; Xiaohong Wang; Yan Li; Panxia Wang; Yue Hao; Wenwen Li; Lei Zhang; Wenjing Su; Jie Qin; Ya Qiu; Junyang Luo (BMC Medical Imaging)
Abstract Background Tuberculosis (TB) is a global health burden, and extrapulmonary TB, particularly urogenital TB, is a significant concern in males. Given the nonspecific clinical manifestations of epididymal and/or testicular TB, this study characterizes the MRI features of this condition to facilitate earlier and more accurate diagnosis. Methods This retrospective study was approved by the ethics committee. We included 14 patients with epididymal and/or testicular TB (diagnosed between January 2015 and September 2024) who underwent contrast-enhanced MRI scans on a 1.5-T scanner. MRI features and clinical characteristics were analyzed by two experienced radiologists. Results Among these 14 patients (median age, 44.5 years), 78.6% of them had epididymal TB with or without testicular involvement, while 21.4% had isolated testicular TB. The most common local symptom was a painful scrotal mass (85.7%), and 64.3% reported fever. TB in other sites was identified in 71.4% patients. T lymphocyte spot test was positive in 57.1% patients, and pathological confirmation was obtained in 42.9%. Most lesions (71.4%) were unilateral. On T1-weighted images, 50% of lesions were isointense and 42.9% were mildly hyperintense. T2-weighted imaging showed hypointense signals in 64.3% of cases. All lesions appeared hyperintense on diffusion-weighted imaging, with 92.9% showing restricted diffusion. Heterogeneous or annular enhancement was observed in 85.7% of lesions. Hydrocele was present in all patients, and 21.4% had abscess formation or fistula. Conclusions MRI provides valuable soft-tissue characterization for diagnosing epididymal and/or testicular TB. Clinical trial number Not applicable.